Some Peculiarities of the Tactics of Investigative (Search) Actions while Investigating Murders Committed in Relation to Domestic Violence - K. A. Shapoval (Bulletin of Kharkiv National University of Internal Affairs, 2021)
Domestic violence is becoming more widespread every day, but few people consider it as a prerequisite for other criminal offenses, among which the most serious and inevitable is murder, i.e. the onset of person’s death. According to the analysis of investigative and judicial practice during the investigation of murders, investigators do not fully investigate the preconditions that contributed to the crime, family relationships, the psychological state of those involved in the murder, etc. Most homicides are investigated and prosecuted without any evidence of domestic violence. Therefore, there is a need to develop a methodology for investigating murders committed in connection with the use of domestic violence, which would contain practical recommendations for conducting certain investigative (search) actions during the investigation of this category of cases.